1995
DOI: 10.1677/joe.0.1440049
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of chromogranin A, chromogranin B (secretogranin I), chromogranin C (secretogranin II) and pancreastatin in plasma and urine from patients with carcinoid tumours and endocrine pancreatic tumours

Abstract: Chromogranins and/or secretogranins constitute a family of water-soluble acidic glycoproteins that are present in almost all endocrine, neuroendocrine and neuronal tissue. Antibodies against chromogranins have been widely used for immunohistochemical staining of endocrine tissue and tumours of neuroendocrine origin. Furthermore, measurements of circulating chromogranin A have been used as a reliable marker for neuroendocrine tumour growth. In this study, we describe the development of specific antibodies again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
177
2
12

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(194 citation statements)
references
References 0 publications
3
177
2
12
Order By: Relevance
“…Although it could be speculated that the detection of a more restricted fragment could correlate to total CgA measurement, it has been shown that the assessment of plasma pancreastatin, produced by cleavage at the 243 and 294 dibasic sites, was less discriminative and of less clinical interest than that of total CgA (Stridsberg et al, 1995). Our results show that the hCgA C-terminal end is particularly affected by degradation, but that proteolysis decreases when moving upstream in the sequence.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Although it could be speculated that the detection of a more restricted fragment could correlate to total CgA measurement, it has been shown that the assessment of plasma pancreastatin, produced by cleavage at the 243 and 294 dibasic sites, was less discriminative and of less clinical interest than that of total CgA (Stridsberg et al, 1995). Our results show that the hCgA C-terminal end is particularly affected by degradation, but that proteolysis decreases when moving upstream in the sequence.…”
Section: Discussionmentioning
confidence: 57%
“…Levels of total circulating hCgA are significantly elevated in phaeochromocytomas, carcinoid and pancreatic endocrine tumours (O'Connor and Deftos, 1986). These data have been confirmed and extended to other neoplasia: neuroblastoma and gastrointestinal tumours (Eriksson et al, 1990;Hsiao et al, 1990;Stridsberg et al, 1995). Other authors have also described how the occurrence of plasma hCgA in prostatic carcinoma may be the sign of an unfavourable evolution (Cussenot et al, 1996;Deftos et al, 1996).…”
mentioning
confidence: 72%
“…The antibodies and the synthesized peptide were used to develop a specific RIA. For preparation of the tracer, the peptide was labeled with 125 I (Amersham International plc, Amersham) using the chloramine-T method as previously described (24). The assay was devised as follows: standards and unknown samples were incubated with a tracer (30 000 c.p.m./tube) and primary antibodies, at a final dilution of 1/45 000, for 3 days at C4 8C.…”
Section: Development Of the Riamentioning
confidence: 99%
“…Ileal carcinoids are composed of enterochromaffin cells that secrete serotonin and tachykinins, which may give rise to hormonal symptoms. Other tumour markers are chromogranin A and vesicular monoamine transporter 1 (Stridsberg et al 1995, Jakobsen et al 2001. The aetiology of ileal carcinoids is unknown.…”
Section: Introductionmentioning
confidence: 99%